Comorbidities and factors associated with central nervous system infections and death in non-perinatal listeriosis: a clinical case series. Issue 1 (December 2016) - Maertens De Noordhout, C.; Devleesschauwer, B.; Maertens De Noordhout, A.; Blocher, J.; Haagsma, J.; Havelaar, A.; Speybroeck, N.
Abstract Background Listeriosis is a rare disease caused by the bacteriumListeria monocytogenes and mainly affects at risk people. Listeriosis can lead to sepsis, central nervous system (CNS) infections and death. The objectives of this study were to describe and quantify comorbidities and neurological sequelae underlying non-perinatal listeriosis cases and to describe the factors associated with death and CNS infections in non-perinatal listeriosis. Methods We retrospectively collected clinical data through computerized, paper or microfilmed medical records in two Belgian university hospitals. Logistic regression models and likelihood ratio tests allowed identifying factors associated with death and CNS infections. Results Sixty-four cases of non-perinatal listeriosis were included in the clinical case series and 84 % were affected by at least one comorbid condition. The main comorbidities were cancer, renal and severe cardio-vascular diseases. Twenty-nine patients (45 %) suffered from a CNS infection and 14 patients (22 %) died during hospitalization, among whom six (43 %) had a CNS involvement. Among surviving patients, eleven suffered from neurological sequelae (22 %) at hospital discharge; all had CNS infection. Five of these patients (45 %) still suffered of their neurological sequelae after a median follow-up of one year (range: 0.08–19). The factor associated with death during the hospitalization was the presence of a severe cardiovascular disease (OR = 4.72, p = 0.015). Two factors inversely related with CNS infections were antibiotic monotherapy (OR = 0.28, p = 0.04) and the presence of renal disease (OR = 0.18, p = 0.02). Conclusions In a public health context these results could be a starting point for future burden of listeriosis studies taking into account comorbidity.